Targeted and untargeted metabolomics provide insight into the consequences of glycine‐N‐methyltransferase deficiency including the novel finding of defective immune function. Issue 18 (19th September 2020) - Eudy, Brandon J.; McDermott, Caitlin E.; Liu, Xiuli; da Silva, Robin P.
Abstract: Fatty liver disease is increasing along with the prevalence of obesity and type‐2 diabetes. Hepatic fibrosis is a major health complication for which there are no efficacious treatment options available. A better understanding of the fundamental mechanisms that contribute to the accumulation of fibrosis is needed. Glycine‐N‐methyltransferase (GNMT) is a critical enzyme in one‐carbon metabolism that serves to regulate methylation and remethylation reactions. GNMT knockout (GNMT ‐/‐ ) mice display spontaneous hepatic fibrosis and later develop hepatocellular carcinoma. Previous literature supports the idea that hypermethylation as a consequence of GNMT deletion contributes to the hepatic phenotype observed. However, limited metabolomic information is available and the underlying mechanisms that contribute to hepatic fibrogenesis in GNMT ‐/‐ mice are still incomplete. Therefore, our goals were to use dietary intervention to determine whether increased lipid load exacerbates steatosis and hepatic fibrosis in this model and to employ both targeted and untargeted metabolomics to further understand the metabolic consequences of GNMT deletion. We find that GNMT mice fed high‐fat diet do not accumulate more lipid or fibrosis in the liver and are in fact resistant to weight gain. Metabolomics analysis confirmed that pan‐hypermethylation occurs in GNMT mice resulting in a depletion of nicotinamide intermediate metabolites. Further, there is a disruption in tryptophan catabolism that prevents adequate immune cell activation in the liver. The chronic cellular damage cannot be appropriately cleared due to a lack of immune checkpoint activation. This mouse model is an excellent example of how a disruption in small molecule metabolism can significantly impact immune function.